Death of a clam digger - Hollis, Lee (Hollis, Lee. Hayley Powell food and cocktails mystery, 2023)
"Food and cocktails columnist Hayley Powell usually reserves judgement for local cuisine, not the people who serve it. But staying neutral isn't so easy when caught between the biggest seafood rivals in town--her BFF Mona Barnes and the successful Leighton clan. Adding to a bitter decades-old surf-turf war between family businesses, a modern Romeo and Juliet story unfolds as Mona's son gets engaged to the daughter of her sworn enemy ... Spiteful patriarch Lonnie Leighton is also steamed about the arrangement--enough to go to dangerous lengths to break it up. At least, until he's discovered face down and dead in the clam flats. With unanswered questions swirling, accusations flying in both directions, and a young couple stuck in the middle, Hayley has bigger fish to fry than determining who sources the best shellfish in Bar Harbor. Because someone wants to get away with murder ... and send whoever else gets in their way to a muddy grave"--